2021
DOI: 10.7759/cureus.17687
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Wells Scores and D-dimer Levels for the Diagnosis of Deep Vein Thrombosis and Pulmonary Embolism in COVID-19: A Retrospective Cohort Study

Abstract: IntroductionDeep vein thrombosis (DVT) and pulmonary embolism (PE) are key complications of coronavirus disease 2019 . The study's primary outcome was assessing the utility of Wells DVT, Wells PE scores, and D-dimers in diagnosing DVT and PE. Secondary outcomes were the risk factors for the development of PE and DVT in COVID-19 patients. Materials and methodsWe compared COVID-19 patients with a positive and negative lower extremity (LE) duplex. A similar approach was made for patients who underwent imaging for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
(65 reference statements)
2
9
0
2
Order By: Relevance
“…However, biomarkers of coagulation (e.g., d-dimer, fibrinogen level, and activated partial thromboplastin time) or inflammation (Leukocyte count, C-reactive protein) failed to discriminate between patients with or without thrombotic complications [ 30 ]. Therapeutic-dose anticoagulation should be reserved for patients with a documented venous thrombotic event or those showing high probability of thromboembolism defined by a Wells score of 3 in suspected deep vein thrombosis and a Wells score of 4 in suspected pulmonary embolism and D-dimers of 500 ng/mL and above [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, biomarkers of coagulation (e.g., d-dimer, fibrinogen level, and activated partial thromboplastin time) or inflammation (Leukocyte count, C-reactive protein) failed to discriminate between patients with or without thrombotic complications [ 30 ]. Therapeutic-dose anticoagulation should be reserved for patients with a documented venous thrombotic event or those showing high probability of thromboembolism defined by a Wells score of 3 in suspected deep vein thrombosis and a Wells score of 4 in suspected pulmonary embolism and D-dimers of 500 ng/mL and above [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Raj et al, a Wells score ≥4 in combination with a D-dimer ≥500 ng/mL showed a sensitivity of 96.1% 25 . Finally, Polo Friz et al analyzed the dichotomized Wells score in 40 COVID-19 patients with suspected PE 26 .…”
Section: Resultsmentioning
confidence: 94%
“…Table 3 shows the characteristics of the studies included. Thirteen studies were included, all of which were retrospective cohort studies 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worrying that in the series described, this complication occurred in patients despite routine heparin prophylaxis. With the more aggressive variant of thrombotic complications observed in lethal cases, extensive microthrombosis of both lungs is noted, extending to the entire respiratory area (Raj et al, 2021). A more detailed follow-up revealed diffuse and severe endothelial and alveolar damage with disruption of alveolar membranes, perialveolar microangiopathy, and widespread microthrombosis with intra alveolar hemorrhages.…”
Section: Introductionmentioning
confidence: 97%